Non-physiological mechanisms influencing disulfiram treatment of alcohol use disorder: A grounded theory study. (1st August 2016) - Newton-Howes, Giles; Levack, William M.M.; McBride, Sam; Gilmor, Moira; Tester, Rachel
Highlights: Abstinence is psychosocial, with Antabuse the marker of the decision not to drink. The act of taking the pill became an act of choosing to have day without alcohol. Take disulfiram was described as empowering or even liberating. Disulfiram gave control over life events, removing rumination on drinking decisions. Abstract: Background: The mechanism of action of disulfiram is not clear and recent systematic reviews have reached differing conclusions. The purpose of this research was to develop a conceptual model of the mechanisms that underpin the effective use of disulfiram in management of alcohol used disorder. Methods: Grounded theory was used, based on anonymized transcripts of in-depth interviews with 14 individual clients who experienced taking disulfiram for alcohol use disorder within the context of a specialized clinic setting from New Zealand. Results: The central concept was that of abstinence being a psychosocial construction, with the taking of disulfiram, being a physical manifestation of the decision not to drink. The main subthemes included the importance of participants believing in the potential for disulfiram producing a negative reaction, the increased autonomy achieved by disulfiram removing the need to ruminate on drinking decisions, and the importance of external structure, routine, and social contact with others to support ongoing engagement with disulfiram therapy. Conclusions: The physiological effects of disulfiram, in particular its adverse reaction when combined with alcohol, explains only part of its effect on problem drinking behaviour. The act of taking a disulfiram pill is also partly symbolic of making an absolute decision not to drink for a short period, allowing people with alcohol use disorder to explore other options for managing life without alcohol. Drug trials involving disulfiram need to treat it not simply as pharmaceutical but as part of a complex psychosocial intervention conducted within a supportive social context.